Analisis Kesesuaian Lahan Rehabilitasi Mangrove di Desa Pasar Banggi, Desa Tireman, dan Desa Kabongan Lor, Kecamatan Rembang - Ain, Rahmayani Kurnia; Pribadi, Rudhi; Suryono, Suryono (Universitas Diponegoro, 2025)
Environmental degradation, coastal abrasion, and pollution are strategic issues in Rembang District. Rembang subdistrict, which includes extensive mangrove areas along its coastline particularly in the villages of Pasar Banggi, Tireman, and Kabongan Lor has become increasingly vulnerable to these environmental challenges. This study aims to evaluate land sustainability in these three villages to support future mangrove rehabilitation planning. Fieldwork was conducted in September 2024 across 14 sampling stations. Data collection included assessments of mangrove vegetation by counting individual trees, identifying species, and measuring relevant environmental parameters. Land suitability analysis was carried out by constructing a mangrove land suitability matrix, assigning weights, and calculating scores based on the degree of suitability. Based on land suitability analysis, Pasar Banggi Village was identified as highly suitable for mangrove survival, Tireman Village as suitable, and Kabongan Lor Village as conditionally suitable. Permasalahan degradasi lingkungan, abrasi dan pencemaran menjadi isu strategis yang ada di Kabupaten Rembang. Kecamatan Rembang yang memiliki kawasan mangrove di sepanjang pesisirnya terutama Desa Pasar Banggi, Tireman, dan Kabongan Lor menjadi kawasan yang rentan. Penelitian ini bertujuan untuk mengetahui kesesuaian lahan yang ada di 3 Desa tersebut sehingga dapat digunakan untuk rencana rehabilitasi selanjutnya. Penelitian dilakukan pada Bulan September 2024 dengan total 14 stasiun. Pengambilan data lapangan dilakukan untuk mengetahui kondisi vegetasi mangrove dengan menghitung jumlah individu, jenis, dan pengukuran parameter lingkungan. Analisis kesesuaian lahan dilakukan dengan pembuatan matriks kesesuaian lahan mangrove, penentuan bobot dan perhitungan skor berdasarkan tingkat kesesuaiannya. Berdasarkan kesesuaian lahan mangrove Desa Pasar Banggi menjadi lokasi yang sangat sesuai untuk kelangsungan hidup mangrove, dengan Desa Tireman masuk dalam kategori sesuai dan Desa Kabongan Lor masuk dalam kategori sesuai bersyarat.